Bibliometric Analysis of Electronic Petitions and Digital Complaint Systems - Judijanto, Loso; Hartati, Tuti (Westscience Press, 2025)
This study conducts a bibliometric analysis of electronic petitions and digital complaint systems, with the objective of delineating the intellectual framework, research progression, and collaborative networks within this expanding domain. The investigation utilized data obtained from the Scopus database (2000–2025) and deployed Bibliometrix (R package) and VOSviewer for performance evaluation and scientific mapping. The findings reveal three primary topic clusters: (1) digital records and health informatics as essential infrastructure; (2) user-centered interaction and citizen participation; and (3) mobile applications and financial integration as nascent frontiers. The United States, Australia, and the Netherlands lead in international collaboration, indicating robust transnational research relationships. The research theoretically integrates e-petition and complaint system studies within a cohesive framework of digital participatory governance, while practically offering insights into the design, policy, and implementation methods for inclusive and responsive e-government systems. Limitations encompass reliance on a singular database and restricted qualitative interpretation, indicating that future study ought to integrate bibliometric mapping with case-based analysis to enhance contextual comprehension.